Age-related changes in nitrogen resorption and use efficiency in the perennial new crop Physaria mendocina (Brassicaceae) - Pastor Pastor, Alejandro (2015)
Domestication of desert-adapted species and their development into perennial crops has been pro-posed as an alternative to increase cropping intensity in arid lands, while reducing nitrogen inputs andlosses. Among traits involved in nitrogen conservation much attention has been drawn to resorption pat-terns. However, understanding of intra-population variability in resorption and nitrogen use efficiencyis required prior to the development of new crops. Here we evaluate age-related changes in resorptionpatterns and nitrogen use efficiency (NUE) within a wild population of Physaria mendocina (Brassicaceae).We generated a relative age index, based on morphological traits, and we use it as an independent vari-able to regress nitrogen concentrations in roots and leaves (green and senesced), nitrogen resorptionefficiency and use efficiency. Nitrogen in green and senesced leaves decrease with age, resorption effi-ciency did not change, and nitrogen use efficiency increased. The lower nitrogen concentration in greenleaves and higher proficiency (lower nitrogen concentrations in senesced leaves) of older plants mightbe due to a decrease in acquisition capacity. Constant efficiency is explained by the lack of differences inconcentration in green and senesced leaves slopes. Higher proficiency in older plants resulted in higherNUE; this relationship would be modulated by nitrogen concentration in green leaves, which, in turn,is controlled by nitrogen availability and acquisition. These findings have implications in the domesti-cation process, since in perennial species biomass production and internal plant nitrogen turnover overmultiple seasons, are central key to physiological functions such as plant re-growth and winter survival.We identified a few questions as directions for future research